2018
DOI: 10.18632/oncotarget.24667
|View full text |Cite
|
Sign up to set email alerts
|

Visceral abdominal fat measured by computer tomography as a prognostic factor for gynecological malignancies?

Abstract: IntroductionObesity is associated with increased incidence of ovarian (OC), cervical (CC) and endometrium cancer (EC). However, the impact of body composition (BC) on overall survival (OS), especially of visceral adipose tissue (VAT) is not yet understood.MethodsIn 189 women with gynecological malignancies (31 OC, 104 CC, 54 EC, mean age 62.9y; mean BMI 26.8 kg/m2; median follow-up 30.7months) with routine staging CT-scans at baseline (mean interval: 4.3 months), densitometric quantification of total (TAT), vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 57 publications
(80 reference statements)
2
30
0
Order By: Relevance
“…Similarly, two recent studies22 25 included only in the systematic review found that lower skeletal muscle index was not correlated with poorer overall survival. Furthermore, two other studies26 27 confirmed the results of the meta-analysis, that the mean skeletal muscle index as a continuous variable was not predictive of overall survival.…”
Section: Resultsmentioning
confidence: 58%
See 4 more Smart Citations
“…Similarly, two recent studies22 25 included only in the systematic review found that lower skeletal muscle index was not correlated with poorer overall survival. Furthermore, two other studies26 27 confirmed the results of the meta-analysis, that the mean skeletal muscle index as a continuous variable was not predictive of overall survival.…”
Section: Resultsmentioning
confidence: 58%
“…The flow diagram is illustrated in Figure 1. Fifteen studies6–12 20–27 were included in this systematic review, of which six studies were included in the meta-analysis 6–12. (Online supplementary Table S2 lists all excluded studies9 18 28–33 and the reasons for exclusion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations